Functional Bioglass—Biopolymer Double Nanostructure for Natural Antimicrobial Drug Extracts Delivery - Negut, Irina; Floroian, Laura; Ristoscu, Carmen; Mihailescu, Cristian N.; Mirza-Rosca, Julia Claudia; Tozar, Tatiana; Badea, Mihaela; Grumezescu, Valentina; Hapenciuc, Claudiu; Mihailescu, Ion N. (MDPI AG, 2020)
Aseptic loosening and periprosthetic infections are the main causes of implant failure. Strategies to mitigate this drawback are therefore mandatory to avoid primary and revision replacement surgeries. A functional bioapatite–biopolymer double nanostructure fabricated by matrix-assisted pulsed laser evaporation to prevent infection of orthopedic and dental implants could promote osseointegration and ensure controlled delivery of natural antimicrobial drugs. The synthesized nanostructure consists of two overlapping layers, the lower from a biocompatible polymer for anticorrosive protection, and the upper of bioactive glass incorporating antimicrobial plant extract, acting as a potential drug delivery system. Morphology, composition, adherence, ability for drug delivery and biological properties (cytotoxicity and antimicrobial effect) were studied. Structures proved compact and stable, conserving a remarkable drug delivery ability for more than 21 days, i.e., enough to ensure long-term microbes’ eradication.
Keywords: drug release; antimicrobial effect; implant protection; bioactive coatings